Oncoplastic breast conservation occupies a niche between standard breast conservation and mastectomy – A population-based prospective audit in Scotland. Issue 10 (October 2019) - Morrow, Elizabeth S.; Stallard, Sheila; Doughty, Julie; Malyon, Andy; Barber, Matthew; Dixon, J. Michael; Romics, Laszlo
Abstract: Introduction: The role of oncoplastic breast conservation (OBC) surgery is not fully defined in terms of whether it is equivalent to standard breast conservation (SBC), or more an alternative to mastectomy, or whether it occupies its own niche somewhere between the two. Therefore, we have carried out a population-based prospective audit of the current OBC practice in Scotland. Methods: All patients diagnosed with breast cancer in the whole of Scotland between 01/01/2014 and 31/12/2015 were prospectively recorded within the National Managed Clinical Networks databases. Patients treated with OBC were compared to patients who had SBC, mastectomy and mastectomy with immediate reconstruction (MIR). Results: 8075 patients were included (OBC:217(2.7%); SBC:5241(64.9%); mastectomy:1907(23.6%); MIR:710(8.8%)). OBC patients were younger than SBC or mastectomy, but older than MIR (p < 0.0001). OBC patients were between SBC and mastectomy patients in terms of clinical and pathological tumour size (all p < 0.001), rates of lobular cancers (v.SBC:p = 0.015 and v.mastectomy:p < 0.001), high-grade tumours (v.SBC:p = 0.030 and v.mastectomy:p = 0.008), ER negative (v.SBC: p = 0.042) and HER-2 positive (v.SBC: p = 0.003) tumours, and nodal metastasis (v.mastectomy: p < 0.001). More OBC patients received (neo)adjuvant chemo- and hormonal therapy (p ≤ 0.001), adjuvant radiotherapy (p = 0.005), trastuzumab (p < 0.001) than SBC. More OBC patients presented through screening (v.mastectomy/MIR: p < 0.0001). Time to surgery from diagnosis was longer for OBC than SBC/mastectomy (p < 0.0001), but shorter than MIR (p = 0.007). Conclusion: This national audit demonstrates that OBC occupies its own niche between SBC, mastectomy and MIR in the surgical treatment of breast cancer in Scotland. We recommend that OBC should be recorded separately in other national breast cancer registries.